Cancer diagnosis and prognosis decoded by blood-based circulating microRNA signatures - Madhavan, Dharanija; Cuk, Katarina; Burwinkel, Barbara; Yang, Rongxi (Frontiers in Genetics, 2013)
In the recent years, circulating microRNAs (miRNAs) have garnered a lot of attention and interest in the field of disease biomarkers. With characteristics such as high stability, low cost, possibility of repeated sampling and minimal invasiveness, circulating miRNAs are ideal for development into diagnostic tests. There have been many studies reported on the potential of circulating miRNAs as early detection, prognostic and predictive biomarkers in cancer. Here, we have reviewed the use of plasma and serum miRNAs as biomarkers for cancer focusing on epithelial carcinomas (prostate, breast, lung, colorectal and gastric cancer) and haematological malignancies (leukaemia and lymphoma). We have also addressed the common challenges that need to be overcome to achieve a successful bench to bedside transition.